Cord bilirubin as a Predictor of Neonatal Hyper bilirubinemia in healthy term babies - Dr. Gouri Rajput; Dr. Sara Dhanawade (Pediatric Review: International Journal of Pediatric Research, 2018)
Objectives: To assess the value of cord blood bilirubin in identifying term healthy babies who develop significant hyperbilirubinemia.Methodology: This Prospective cohort study, conducted from May 2016 to September 2016 in a tertiary care hospital included 100 term healthy breastfed babies without Rh incompatibility or significant illness. Cord bilirubin was estimated in all babies. Neonates were followed up daily for 5 days for hyperbilirubinemia. Serum bilirubin levels were estimated on day 5 in all babies. Significant hyperbilirubinemia was defined as bilirubin > 15 mg/dl after 72 hours.Results: Mean cord bilirubin was 2.8 +2.4 mg /dl in those who developed hyperbilirubinemia and 2.5+2.91 mg/dl in those who did not. Clinically detectable jaundice was present in 72%.Twenty-two percent babies developed hyperbilirubinemia. Peak serum bilirubin of babies who developed significant hyperbilirubinemia was 23+ 2.8mg/dl at 120 hours. Cord bilirubin of > 2mg /dl was present in 64 babies and 19 (29%) developed hyper bilirubinemia. Cord bilirubin < 2mg was present in 36 and only 3(8%) developed hyper bilirubinemia (p=0.018). The sensitivity was 86% specificity was 40%, positive predictive value was 29% and negative predictive valuewas 91% at critical cord bilirubin value of >2mg/dl. ABO incompatibility was significantly associated with hyperbilirubinemia (p=0.0006).Conclusion: Cord bilirubin can be a good predictor of hyperbilirubinemia. Neonates with cord bilirubin < 2mg/dl are probably safe for early discharge and those with bilirubin levels >2 mg/dl need close follow up.